Placental ARFI elastography and biometry evaluation in bitches - Simões, Ana Paula Rodrigues [UNESP] (2020)
Placental rigidity and biometry of twelve pregnant bitches were evaluated using B-mode and Acoustic Radiation Force Impulse (ARFI) ultrasonography, performed once daily, from day 15 of gestation until parturition. Speciﬁc software (Virtual Touch Tissue Quantiﬁcation® VTTQ and Virtual Touch Tissue Imaging Quantiﬁcation® VTTIQ) were used. Values for results for variables were correlated and regression models related to gestational day were used to make evaluations. Maternal-fetal placental thickness increased to day 63 (P<0.0001; R² = 0.91); maternal placental thickness increased until day 40 (P = 0.0340; R² = 0.54); and fetal placental thickness increased to day 50 (P<0.0001; R² = 0.83) of gestation. Shear wave velocity (SWV) of the dorsal (P<0.0010) was greater than lateral, which in turn was greater (P = 0.020) than the ventral area. The SWV of the dorsal area as determined using VTTQ, decreased from day 21–35 and increased to day 56 of gestation (P = 0.0291; R² = 0.4021); lateral SWVdecreased from day 24–45 and increased until the time of parturition (P<0.001; R² = 0.6055). The SWV of the dorsal area, as determined using VTTIQ, decreased from day 21–43 and then increased to day 60 of gestation (P = 0.0016; R² = 0.5075); and ventral area SWV increased from day 21–23 and decreased until the time of parturition (P<0.001; R² = 0.8055). Placental alterations reﬂect structural and biochemical gestational adaptations and can become useful techniques for obstetrics.